### Answers − Solving quadratics of the form ax2 + bx + c = 0 by factorising first

#### 1.   Solve 2x2 + 10x + 8 = 0

 i. From answer 1 in Factorising Quadratics − 2 the factors are: (2x + 2)(x + 4) ii. So (2x + 2)(x + 4) = 0
 iii. Either

Verify by putting these two values of x into 2x2 + 10x + 8

#### 2.   Find the values of x where 3x2 + 21x + 18 = 0

 i. From answer 2 in Factorising Quadratics − 2 the factors are: (3x + 3)(x + 6) ii. So (3x + 3)(x + 6) = 0
 iii. Either

Verify by putting these two values of x into 3x2 + 21x + 18

#### 3.   Solve 4x2 + 20x − 24 = 0

 i. From answer 3 in Factorising Quadratics − 2 the factors are: (4x − 4)(x + 6) ii. So (4x − 4)(x + 6) = 0
 iii. Either

Verify by putting these two values of x into 4x2 + 20x − 24

#### 4.   Find the values of x where 2x2 + 9x − 56 = 0

 i. From answer 4 in Factorising Quadratics − 2 the factors are: (2x − 7)(x + 8) ii. So (2x − 7)(x + 8) = 0
 iii. Either

Verify by putting these two values of x into 2x2 + 9x − 56

#### 5.   Solve 5x2 − 20x − 60 = 0

 i. From answer 5 in Factorising Quadratics − 2 the factors are: (5x + 10)(x − 6) ii. So (5x + 10)(x − 6) = 0
 iii. Either

Check by putting these two values of x into 5x2 − 20x − 60

#### 6.   Find the values of x where 3x2 − 21x + 36 = 0

 i. From answer 6 in Factorising Quadratics − 2 the factors are: (3x − 12)(x − 3) ii. So (3x − 12)(x − 3) = 0
 iii. Either

Check by putting these two values of x into 3x2 − 21x + 36

#### 7.   Solve 3x2 − 40x + 48 = 0

 i. From answer 7 in Factorising Quadratics − 2 the factors are: (3x − 4)(x − 12) ii. So (3x − 4)(x − 12) = 0
 iii. Either

Check by putting these two values of x into 3x2 − 40x + 48

back to: